Impact of informal trade on labor employability in the Peruvian Amazon economy - Paredes-Valverde, Yolanda (2024)
Informal trade plays a vital role in the economy by providing employment opportunities to those seeking to meet their basic needs. Therefore, the objective was to assess the impact of informal trade on labor employability in the Peruvian Amazon. A descriptive cross-sectional study was conducted with a sample of 421 street vendors from streets, avenues, and market surroundings. Data collection was carried out through a survey, whose metrics were determined by content validity and reliability processes. The results indicate that most participants were between 31 and 40 years old, predominantly women, had secondary education, and were Peruvian nationals. Regarding informal trade, most were self-employed and earned daily incomes ranging from 100 to 500 new soles. Street vending was predominant, with snacks and meals being notable products sold. Finally, it was concluded that informal trade in Madre de Dios generates 1,636 direct jobs, representing 2.1% of the population. The majority are women aged 31-40 with secondary education, earning between 100 and 1,000 soles, and working between 8 to 10 hours daily. The findings highlight the need for targeted policies to support informal traders, particularly women, and enhance economic resilience.